Internet-Based Advisory System for Automotive Spare Parts Industry - Yap, Jeremy Yee Wei (2000)
The purpose of this project is to design an e-commerce website, suitable for the current needs in automobile spare parts industry. A current survey is done on some local and international automobile spare parts websites. The review shows that this websites have some weakness and limitations. Based on the limitations, this system is designed to overcome the problems and try to satisfy user needs. The special element about this system is that it has an advisory system and portal link. This advisory system is able to recommend suitable spare parts for user. The website will then link user in the relevant company to buy the recommended spare parts. Finally, this project has recommended some future design and considerations to further enhance the development of future project.